2012
DOI: 10.3945/ajcn.112.045708
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tumor burden and subsequent surgical resection on skeletal muscle mass and protein turnover in colorectal cancer patients

Abstract: Background: Cachexia is a consequence of tumor burden caused by ill-defined catabolic alterations in muscle protein turnover. Objective: We aimed to explore the effect of tumor burden and resection on muscle protein turnover in patients with nonmetastatic colorectal cancer (CRC), which is a surgically curable tumor that induces cachexia. Design: We recruited the following 2 groups: patients with CRC [n = 13; mean 6 SEM age: 66 6 3 y; BMI (in kg/m 2 ): 27.6 6 1.1] and matched healthy controls (n = 8; age: 71 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 40 publications
2
91
1
Order By: Relevance
“…As the preferred method of treatment, surgery can achieve resection of the tumor to avoid skeletal muscle consumption originating from the tumor burden (24). However, a significant association between surgical cancer treatment and the development of sarcopenia was not observed in the present study.…”
Section: Discussioncontrasting
confidence: 54%
“…As the preferred method of treatment, surgery can achieve resection of the tumor to avoid skeletal muscle consumption originating from the tumor burden (24). However, a significant association between surgical cancer treatment and the development of sarcopenia was not observed in the present study.…”
Section: Discussioncontrasting
confidence: 54%
“…Two previous short term studies (<6 hours) using a primed constant infusion of isotope tracer have shown that skeletal muscle protein FSR may be reduced in the fed state in patients with lung cancer (9) or may be unchanged (colorectal cancer) but with a blunted response to intravenous infusion of amino acids (2). Any potential reduction in muscle protein FSR would be expected to be more apparent during the present protocol than during a short-term infusion protocol as the oral tracer design incorporates the potentially cumulative anabolic effect of many meals over the one week protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of skeletal muscle mass in cancer is well described (1)(2)(3) and is a defining characteristic of the cachexia syndrome (4). Low muscle mass is associated with a variety of clinical consequences including prolonged hospitalization, reduced mobility, and increased chemotherapy toxicity (5).…”
Section: Introductionmentioning
confidence: 99%
“…Blood samples were precipitated with perchloric acid and the supernatant was neutralized before purification by cation exchange chromatography. The subsequent eluent was dried under nitrogen before derivatizing the amino acids to their tert-butyldimethylsilyl derivatives using standard techniques (21). Concentrations and enrichments were determined by gas chromatographymass spectrometry (Trace DSQ; Thermo Scientific, U.K.), with norleucine and d 2 -phenylalanine used as internal standards.…”
Section: Leg Protein Turnovermentioning
confidence: 99%
“…These benchmarks were based on reports that serum CRP concentrations .1.35 mg $ mL 21 are associated with increased levels of IL-6 and TNF-a in obese individuals (16). All individuals not meeting these criteria were excluded from participating.…”
mentioning
confidence: 99%